Negosiasi Kepentingan Dalam Perumusan RPJMD DIY 2017-2022 Dalam Kerangka Advocacy Coalition Framework: Negotiation of Interest in RPJMD DIY 2017-2022 Policy Formulation Using Advocacy Coalition Framework - Kamim, Anggalih B.M; Amal, Ichlasul; Khandiq, M. Rusmul (Jurnal Borneo Administrator, 2019)
An exploration of policy changes and learning and interest negotiation in formulating policy are useful for mapping the process of compromising between the authorities and citizens. The study aims to explore the relations of external actors and local governments as a reflection of the state in the formulation of 2017-2022 DIY development planning policies to ensure no policies that favor the interests of certain groups. This research was conducted in qualitative research methods. This research was framed by a case study method. The research was conducted in agencies/ companies/ academics/ donor institutions/ parliament and the community involved and affected in the process of formulating DIY development planning policies. Research showed that there were some disadvantages of ACF model. The first disadvantage related to the inability of the ACF to explain the position of one of the "plural-faced" parties. The next disadvantage was the fact that ACF could not explain in detail the exact reason behind the formation of a coalition. The last disadvantage was that the ACF could not explain the dispersal of movements in a coalition. Keywords: RPJMD DIY 2017-2022, Advocacy Coalition Framework, Policy Coalition Abstrak Penggalian policy change and learning serta negosiasi kepentingan dalam perumusan kebijakan berguna untuk memetakan proses kompromi penguasa dan warga. Studi untuk menggali dan mendalami relasi aktor eksternal dan pemerintah daerah sebagai cerminan negara dalam perumusan kebijakan perencanaan pembangunan DIY 2017-2022 menjadi penting untuk memastikan tidak adanya kebijakan yang berpihak pada kepentingan kalangan tertentu. Penelitian ini dilakukan dengan metode penelitian kualitatif. Penelitian ini dibingkai dengan metode studi kasus. Penelitian dilakukan di instansi/perusahaan/kalangan akademisi/lembaga donor/parlemen serta kalangan masyarakat yang terlibat dan terdampak dalam proses perumusan kebijakan perencanaan pembangunan DIY. Penelitian menunjukan bahwa dalam model ACF terdapat beberapa kekurangan. Kekurangan pertama berkaitan dengan ketidakmampuan ACF untuk menjelaskan posisi salah satu pihak yang â€œberwajah majemukâ€. Kekurangan berikutnya adalah ACF tidak dapat menjelaskan dengan detail alasan terbentuknya sebuah koalisi secara pasti. Kekurangan terakhir yaitu ACF tidak dapat menjelaskan terpencarnya gerakan dalam suatu koalisi. Kata Kunci : RPJMD DIY 2017-2022, Advocacy Coalition Framework, Koalisi Kebijakan